Teaching Assistants in International Schools: Perceptions and Perspectives - Lehman, Clayton (Widya Mandala Catholic University Surabaya, 2020)
This research study occurred because of the many observations made by the researcher while working in international schools in East and Southeast Asia. Although multiple studies have investigated teaching assistants in public schools, there is little research dedicated to the study of teaching assistants in international schools. The purpose of this research study was to look at classroom practices, student language acquisition, professional development, and teaching assistant wellbeing in international schools through the lenses of locally-hired teaching assistants and to discover what they consider to be barriers in their positions as a teaching assistant. Further, comparisons were made between teaching assistants in English-only and multi-lingual schools and between teaching assistants in schools that are for-profit and non-profit. Data acquisition for this mixed-methods study occurred through a thirteen question survey that was completed by 135 teaching assistants working in international schools in East and Southeast Asia. The main findings of this research study were that many teaching assistants in international schools desire relevant professional development, fairer working environment, more equitable salary conditions, and more professional and career opportunities.